Conhecimento, identidade e poder na comunidade muçulmana sunita do Rio de Janeiro - Chagas, Gisele Fonseca (2006)
This dissertation focuses on the role of different forms of religious knowledge in both the constitution and legitimization of power relations and the construction of religious identities in the Sunni Muslim community in Rio de Janeiro. This analysis deals with the tensions between the local religious experiences and the normative tradition enshrined in doctrinal texts and ritual practices. Religious knowledge is continuously mobilized by the local religious authorities as both disciplinary devices and instances of legitimization of their religious authorities. Religious knowledge is differently appropriated and inscribed in the social practices of the members of the Muslim community of Rio de Janeiro according to their gender, ethnicity and social class. Therefore, the various forms of diffusion, appropriation and mobilization of religious knowledge create cumulative differences that give different positions, powers and identity to the members of the Sunni community